Provenance and Annotation of Data and Processes: Second International Provenance and Annotation Workshop, IPAW 2008, Salt Lake City, UT, USA, June 17-18 2008 - Freire, Juliana; Koop, David (Lecture Notes in Computer Science, 2008)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Provenance and Annotation Workshop, IPAW 2008, held in Salt Lake City, UT, USA, in June 2007. The 14 revised full papers and 15 revised short and demo papers presented together with 2 keynote lectures were carefully reviewed and selected from 40 submissions. The paper are organized in topical sections on provenance: models and querying; provenance: visualization, failures, identity; provenance and workflows; provenance for streams and collaboration; and applications.